If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3x = -6x + -8 Reorder the terms: -3x = -8 + -6x Solving -3x = -8 + -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. -3x + 6x = -8 + -6x + 6x Combine like terms: -3x + 6x = 3x 3x = -8 + -6x + 6x Combine like terms: -6x + 6x = 0 3x = -8 + 0 3x = -8 Divide each side by '3'. x = -2.666666667 Simplifying x = -2.666666667
| 3/p=9 | | 4(x+8)=-24 | | 3x(3+2)=7 | | 0.13(c+50.00)=30.00 | | -2.2+1.1x=0 | | 2p+5p=14 | | 0.13(c+50.00)=24.94 | | 4(x-3)+(3x)/2=3x+5 | | 2y-14=24 | | -1.6=1.6z+16 | | 8xy/5(((x^3)y)^1/4) | | 3x(3+2)-7= | | -8x=-4x+9 | | -6(x-7)=-18 | | 11/18=? | | 1.9=-0.95(b+6) | | -5.6=h/5+12.2 | | x^2-12x-252=0 | | 5/2=? | | 11/2=? | | 5/11=? | | 1/(t+1)^2=1 | | -8x+3+9x=-9x-9 | | 2/3x+1/2x+1/5x=1 | | -9x-1=-10x-7 | | cos(x)=0.25 | | (1/3X)+3/4=Y | | 9x=-10x+9 | | 7/2=42/n | | -10x=8x+4 | | -4x-5+7x=-5x+7 | | 4-3n=19 |